The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ol9005882
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Co(II)-Catalyzed Cyclopropanation with Succinimidyl Diazoacetate: General Synthesis of Chiral Cyclopropyl Carboxamides

Abstract: [Co(P1)] is an effective catalyst for asymmetric cyclopropanation with succinimidyl diazoacetate. The Co(II)-catalyzed reaction is suitable for various olefins, providing the desired cyclopropane succinimidyl esters in high yields and excellent diastereo- and enantioselectivity. The resulting enantioenriched cyclopropane succinimidyl esters can serve as convenient synthons for the general synthesis of optically active cyclopropyl carboxamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 53 publications
2
44
0
1
Order By: Relevance
“…The catalytic system showed an excellent efficiency also with use of diazosulfones, [76] α-nitrodiazoacetates, [80] succinimidyl diazoacetate [81] and α-cyanodiazoacetate [82] (Figure 7). The synthesis of cyclopropanes bearing the different R and RЈ groups listed in Figure 7 represents an important synthetic result for several reasons.…”
Section: Cobalt-catalysed Reactionsmentioning
confidence: 99%
“…The catalytic system showed an excellent efficiency also with use of diazosulfones, [76] α-nitrodiazoacetates, [80] succinimidyl diazoacetate [81] and α-cyanodiazoacetate [82] (Figure 7). The synthesis of cyclopropanes bearing the different R and RЈ groups listed in Figure 7 represents an important synthetic result for several reasons.…”
Section: Cobalt-catalysed Reactionsmentioning
confidence: 99%
“…In spite of the fact that the stoichiometric condensation reaction of cobalt(II) porphyrin complexes with ethyl diazoacetates (EDA) was already disclosed by Johnson and co-workers in 1975, 15a only recent years have witnessed significant impact of cobalt(II) porphyrins to the cyclopropanation of olefins with diazo reagents. [16][17][18][19][20][21][22][23] The EPR, ESI-MS as well as DFT studies revealed that the cobalt(II)-porphyrin-mediated cyclopropanation of olefins with diazoesters proceeds via the formation of the Fischer-type radical carbene II followed by a stepwise radical addition of an olefin (1) and cyclization cascade toward the corresponding cyclopropanes 3 and 4 (Scheme 1). 17,18 The "terminal radical carbene species" II and the "bridging carbene species" III were proposed to exist as redox isomers and in dynamic equilibrium with each other, although the latter was determined to be thermodynamically somewhat more stable according to DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cobalt(II) complexes of Zhangs' chiral porphyrins having amide functionality have emerged as general and highly diastereoand enantioselective catalysts for the cyclopropanation of olefins with diazo reagents. [19][20][21][22][23] All these developments, as well as our continuing interest in metal-porphyrins in asymmetric catalysis, …”
Section: Introductionmentioning
confidence: 99%
“…(3)]. [10] The intermediate metallocarbene species can also be guided to insert into X À H bonds (X = heteroatom), including that of an alcohol, thiol, or amine group. [11] Complementary to these transformations-based on an initial direct reaction between the diazoalkane and metal-is non-redox activation of diazoalkanes using Lewis acids.…”
Section: Introductionmentioning
confidence: 99%